Medicolegal Issues in Obstetrics and Gynaecology (Springer International Publishing, 2018)
This book highlights minimum standards relating to the management of different conditions in the practice of Obstetrics and Gynaecology. The editors explore clinical governance issues, common causes of as well as ways to avoid litigation. The UK is experiencing a dramatic increase in medico-legal claims. The 4 main reasons for litigation are: accountability, the need for an explanation, concern with standards of care and compensation. However the decision to take legal action is determined not only by the original injury, but failure to provide information, an explanation and an apology. Insensitive handling of an injury and poor communication after the original incident increases the risk of litigation and erodes the patient-doctor relationship. Doctors almost never deliberately cause harm to patients, however increasingly claims are being defended successfully. This book is invaluable to clinicians and lawyers alike and raises awareness of how to avoid facing clinical negligence claims in our day to day practice.